Effect of pneumococcal conjugate vaccine on prevalence of otitis media with effusion among children in Vietnam. Issue 36 (26th August 2022) - Toizumi, Michiko; Satoh, Chisei; Quilty, Billy J.; Nguyen, Hien Anh Thi; Madaniyazi, Lina; Le, Lien Thuy; Ng, Chris Fook Sheng; Hara, Minoru; Iwasaki, Chihiro; Takegata, Mizuki; Kitamura, Noriko; Nation, Monica Larissa; et al.
Highlights: Pneumococcal conjugate vaccine reduced otitis media with effusion in infants. Otitis media with non-vaccine type was transiently increased in post-vaccine period. Timely vaccination and higher herd immunity can increase the effect. Abstract: Purpose: Otitis media with effusion (OME) is common in young children and is associated with Streptococcus pneumoniae infection. We aimed to determine the impact of pneumococcal conjugate vaccine (PCV) introduction on the prevalence of OME and OME associated with vaccine-type (VT) or non-VT. Methods: Population-based cross-sectional surveys were conducted in pre- (2016) and post-PCV periods (2017, 2018, and 2019) at selected communes in Nha Trang, Vietnam. For each survey, we randomly selected 60 children aged 4–11 months and 60 aged 14–23 months from each commune. Nasopharyngeal sample collection and tympanic membrane examination by digital otoscope were performed. S. pneumoniae was detected and serotyped by lytA qPCR and microarray. Odds ratios (OR) and 95% confidence intervals (CIs) were calculated using Firth's logistic regression, stratified by age group. Results: Over the four surveys, 2089 children had a bilateral ear examination. Compared to pre-PCV, the prevalence of OME reduced in 2018 (OR 0.51, 95 %CI 0.28–0.93) and in 2019 (OR 0.53, 95 %CI 0.29–0.97) among the <12-month-olds, but no significant reduction among the 12–23-month-olds. The prevalence of OME associated with VT pneumococcus decreased in 2018 and 2019 (2018: OR 0.14, 95 %CI 0.03–0.55; 2019: OR 0.20, 95 %CI 0.05–0.69 in the <12-months-olds, 2018: OR 0.05, 95 %CI 0.00–0.44, 2019: OR 0.41, 95 %CI 0.10–1.61 in the 12–23-months-olds). The prevalence of OME associated with non-VT pneumococcus increased in the 12–23-month-olds in 2017 (OR 3.09, 95 %CI 1.47–7.45) and returned to the pre-PCV level of prevalence in 2018 and 2019 (OR 0.94, 95 %CI 0.40–2.43 and 1.40, 95 %CI 0.63–3.49). Conclusion: PCV10 introduction was associated with a reduction of OME prevalence in infants but not in older children.